Solitary wave transformation, breaking and run-up at a beach - Borthwick, A; Ford, M; Weston, B; Taylor, P; Stansby, P (2006)
A validated one-dimensional Boussinesq-non-linear shallow water equations numerical model was used to investigate the interaction of solitary waves with beaches. The numerical model requires two adjustable parameters: the bed friction coefficient and a wave breaking parameter. Excellent agreement was achieved between the numerical predictions of solitary wave transformation and run-up at a plane beach with two sets of high-quality laboratory measurements: one a large number of experiments in a wave flume by Synolakis, the other in the UK Coastal Research Facility. A parameter study investigated the effect of uniform offshore water depth, bed friction and bed slope on solitary wave run-up. A uniform water depth may be associated with a continental shelf region. The non-dimensional run-up was found to be an asymptotic function of non-dimensional wave amplitude at high and low values of initial wave steepness. Both asymptotes scale as (R/ho) ∼ α(Ao/h o)β where R is run-up (defined as the vertical elevation reached by the wave uprush above still water level), Ao is the offshore wave amplitude and ho is the uniform depth offshore of the beach. The empirical coefficients α and β depend on the beach characteristics. The model is then used to simulate the interaction of a full-scale tsunami event with an idealised beach profile representative of a beach in Eastern Kamchatka.